(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2019)
The present study evaluated the antioxidant and cytotoxic activities of methanolic extract of aerial parts of Adiantum capillus-veneris L. and its different solvent fractions. The in vitro antioxidant activity was assessed by using 2,2’-diphenyl-1-picrylhydrazyl (DPPH) radicals. The analysis revealed that ethyl acetate soluble fraction had the highest DPPH radicals scavenging property with IC50 value of 1.05 μg/ml as compared to positive control ascorbic acid (IC50 = 1.34 μg/ml). In addition, ex vivo cytotoxicity assay of A. capillus-veneris L. extract and its different fractions were performed against HELA cells line where 5-Fluorouracil was used as positive control. The result demonstrated that ethyl acetate and n-hexane soluble fractions showed prominent cytotoxicity with IC50 value of 5.68 μg/ml and 17.15 μg/ml, respectively. The study affirmed that superior antioxidant and cytotoxic activities were shown by ethyl acetate soluble fraction of methanolic extract of aerial parts of A. capillus-veneris L. growing in Bangladesh which indicate the presence of bioactive phytoconstituents in the extractives. Dhaka Univ. J. Pharm. Sci. 18(2): 217-222, 2019 (December)